Kajian Erosi Tanah dan Teknik Konservasi Tanah di Sub DAS Krueng Pirak Kabupaten Aceh Utara - Tiar Munzir; Halim Akbar; M. Rafli (Agrium, 2019)
Land, as a natural resource, has various pressures along with the increase in the human population which has caused a decrease in the quality and land productivity. Decreasing soil quality is caused by nutrients that are washed away by rain and erosion mainly occurs on land that does not apply appropriate conservation management. The rate of erosion and sedimentation in an area illustrates the condition of the watershed management system. This study aims to predict the rate of soil erosion in the Krueng Pirak watershed in North Aceh Regency. The method used in this study is the survey method as follows: preparation, observation, data analysis and presentation of results. The results showed that the calculation of erosion predictions in the Krueng Pirak sub-watershed in North Aceh had different predictive values for each Land Mapping Unit (LMU). The highest erosion prediction is in LMU21 of 882.38 tons / ha / year with coconut vegetation, while the lowest is in LMU14 which only has 0.29 tons / ha / year. This happens because of the low carbon content of forest vegetation. For the Krueng Pirak sub-watershed area, there are several LMU areas that need to be preserved, including LMU2, LMU4, LMU6, LMU9, LMU10, LMU13, LMU15, LMU16, LMU17 and LMU21. This is because the value of predicted erosion in this area exceeds acceptable erosion values. Some conservation efforts that need to be done are in LMU 11 by integrating rubber plants with cassava plants. PL 12, SPL 13, SPL 15 by integrating the main crops with corn, upland rice, cassava, peanuts and plant residues used as mulch. Conservation in LMU16 and LMU21 is carried out by reforestation by covering the soil at the beginning of the year, while in LMU17 conservation is done by combining teak plantations with pea and green bean plants. Keywords: Sub-watershed, Prediction of Erosion, Conservation, LMU